When the Voice of the Refugee is Heard: Sharing Experiences of Detention in Refugee Tales IV - Francisco Fuentes Antrás (Atlantis)
Refugee Tales IV, edited by Anna Pincus and David Herd and published in 2021, is the fourth volume to date of the Refugee Tales short-story collections. While these stories are told by individuals who have been in detention centers, it is renowned writers such as Dina Nayeri and Robert Macfarlane who generally help these refugees and asylum seekers capture their experiences on paper. The project was set up and is organized by the Gatwick Detainees Welfare Group “as a response to the silence that surrounded indefinite immigration detention in the U.K. [and other countries around the world]” (Herd 2017, 113), which criminalizes the asylum process, “mak[ing] the commitment of a crime (for instance, trying to leave the country under false papers) so much more likely” (117). In this article, I will explore how the short stories in Refugee Tales IV contribute to helping refugees and asylum seekers achieve a space of self-determination where their stories, which are often disesteemed or ignored, can be heard. By emulating some of the main themes and features of The Canterbury Tales, these stories shed light on the traumatic experiences many refugees face in the U.K. and other countries with regard to their indefinite detention and a legal system that marginalizes them. I will pay particular attention to the various forms in which the individuals express the impotence of not being able to decide things for themselves, as well as the ways in which the act of storytelling allows them to occupy a literary space from where to speak up and become active agents.